AN EMPIRICAL ANALYSIS OF THE IMPACT OF CURRENT RATIO AND DEBT-TO-EQUITY RATIO ON RETURN ON ASSETS: EVIDENCE FROM PT BEKASI FAJAR INDUSTRIAL ESTATE TBK (2022-2024) - Irnando, Bagus Yohan; Saputra, Febrian Eko (GoAcademica Research dan Publishing, 2025)
This research investigates the relationship between the Current Ratio (CR), Debt-to-Equity Ratio (DER), and Return on Assets (ROA) at PT Bekasi Fajar Industrial Estate Tbk throughout the 2022–2024 period. The study was motivated by post-pandemic financial performance fluctuations that emphasize the necessity of assessing liquidity and capital structure to determine their impact on profitability. A quantitative approach was applied using multiple linear regression analysis. The dataset comprised secondary information drawn from the company’s annual financial statements, which were retrieved from the official website of the Indonesia Stock Exchange (IDX). The findings reveal that the significance values of the Current Ratio (0.696) and the Debt-to-Equity Ratio (0.390) exceeded the 0.05 threshold, implying that neither variable individually affects Return on Assets (ROA) in a statistically significant manner. The F-test result of 0.581 (>0.05) indicates that both variables collectively exert no significant influence on ROA. The coefficient of determination (R²) value of 0.114 suggests that these two independent variables jointly explain only 11.4% of the variation in ROA, while the remaining 88.6% is attributed to other factors not examined in this study.